The Influence of Work Environment and Job Satisfaction on Teacher Performance: The Mediating Role of Work Motivation at Senior High School - Sabilah Hidayati; Putri Kemala Dewi Lubis (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to examine the influence of the work environment and job satisfaction on teacher performance, with work motivation as an intervening variable among teachers at SMA Negeri 2 Percut Sei Tuan. The study was motivated by the less-than-optimal work environment in supporting the learning process and teachers’ dissatisfaction with salaries and welfare benefits. A quantitative approach with an ex post facto design was employed. The population consisted of all 54 teachers at SMA Negeri 2 Percut Sei Tuan. Using a saturated sampling technique, all population members were selected as research participants. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.29. The results showed that the work environment had no significant direct effect on teacher performance. However, it had a positive and significant effect on work motivation. Job satisfaction positively and significantly affected both teacher performance and work motivation. In addition, work motivation had a positive and significant effect on teacher performance. The mediation analysis revealed that work motivation did not significantly mediate the relationship between the work environment and teacher performance, nor the relationship between job satisfaction and teacher performance. The findings indicate that job satisfaction and work motivation are important factors in improving teacher performance. Although the work environment does not directly affect performance, it contributes to enhancing teachers’ motivation. Therefore, schools should prioritize strategies that strengthen job satisfaction and work motivation to improve teacher performance.